Konsepsi Raja Melayu dalam Hikayat Petualangan Ajaib Hikayat Kemala Bahrain - Rizqi Handayani (Manuskripta, 2020)
Abstract: This article explains the views of the Malay community regarding the concept of a king in one of the magical adventure stories, entitled Hikayat Kemala Bahrain ML 443 (HKB). HKB is one of the classic Malay magical adventures stored in the National Library of the Republic of Indonesia. HKB tells about the adventures of a king in finding his identity as the heir to the kingdom. The results of this study indicate that HKB carries the idea of ​​the Malay king as the caliph on earth (Ḍillullah fī al-‘ālam). However, in formulating the concept of king's leadership, the Malay community was still trapped in the idea of ​​god-king spiritualism (devarāja spiritualism) which became one of the criteria attached to the Malay king. Based on the king's conception presented by HKB, it is clear that the Malay worldview aspires to a leader or king who upholds political and state ethics based on noble moral values ​​that are relevant to various situations and conditions. --- Abstrak: Artikel ini menjelaskan pandangan masyarakat Melayu mengenai konsep raja dalam salah satu hikayat petualangan ajaib, yang berjudul Hikayat Kemala Bahrain ML 443 (HKB). HKB merupakan salah satu hikayat petualangan ajaib melayu klasik yang tersimpan di Perpustakaan Nasional RI. HKB bercerita tentang petualangan seorang raja dalam menemukan identitas dirinya sebagai pewaris kerajaan. Penelitian ini merupakan penelitian kepustakaan. Hasil penelitian ini menunjukkan bahwa HKB mengusung gagasan tentang raja Melayu sebagai khalifah di muka bumi (Ḍillullah fī al-‘ālam). Namun, dalam merumuskan konsep kepemimpinan raja, masyarakat Melayu masih terjebak pada gagasan tentang spiritualisme dewa-raja (devarāja spiritualism) yang menjadi salah satu kriteria yang melekat pada raja Melayu. Berdasarkan pada konsepsi raja yang ditampilkan HKB maka terlihat jelas bahwa pandangan dunia Melayu mencita-citakan pemimpin atau raja yang menjunjung tinggi etika politik dan kenegaraan yang berbasis pada nilai-nilai moral yang luhur yang relevan dengan berbagai situasi dan kondisi. Keywords: Magical Adventure Stories, Malay King Concept, Leader Ethics, Hikayat Kemala Bahrain. Kata Kunci: Hikayat Petualangan Ajaib, Konsepsi Raja Melayu, Etika Kepemimpinan, Hikayat Kemala Bahrain.